КРЕАТИВЛИКТИҢ ТЕОРИЯЛЫҚ ТӘРЕПТЕН ҮЙРЕНИЛИЎИ - Худайбергенова, Г. (SCIENCE and SOCIETY, 2019)
The author of the article describes the problem of creativity and its study by foreign scientists, as well as the factors affecting the formation of personal creativity.